1
$\begingroup$

I encounter the following recurrence relations when trying to find a general formula for the derivative of $f(x) = (1 + e^x)^{-1}$ ,

for $n\geq 0$,

\begin{align*} a(0,1) &= 1,\\ a(n,0) &= 0, \quad \\ a(n+1,k) &= (k - 1)a(n, k - 1) - a(n,k),\quad 1 \leq k \leq n+1, \\ a(n + 1,n+2) &= (n+1)a(n,n+1), \end{align*} For $n \geq 0$, according to that post, the solution seems to be $$a(n,k) = (-1)^n \sum_{j = 0}^{k - 1}(-1)^j\binom{k - 1}{j}(j+1)^n,\quad 0 \leq k \leq n+1$$ but I don't know how to get there. I never encounter recurrence relation of this form before.

So here are my questions.

  1. Is there any method to solve this type of recurrence? If any, would you mind to tell me the book/reference on this topic might be.
  2. I'm not sure about this, but is the solution to the problem unique? I think it is, by tring to apply the relations.

Most importantly, how to find the solution above? Any help would be appreciated.

$\endgroup$
  • $\begingroup$ That recurrence reminds me of the ones for Stirling numbers. $\endgroup$ – marty cohen Oct 31 '19 at 12:32
0
$\begingroup$

If I had to solve this (I don't have to since you are asking for a method, not a solution), I would use a two-variable generating function In the form

$A(x, y) =\sum_{i=0}^{\infty}\sum_{j=0}^{\infty} a(i,j)x^iy^j $

and see what properties of A follow from the recurrence.

$\endgroup$
  • $\begingroup$ I have tried this, but (if I'm not mistaken) give me (one of them) the following infinite sum $$\sum_{n = 0}^\infty (n + 1)a(n,n + 1)x^{n + 1} y^{n + 2} = \sum_{n = 0}^\infty n! x^{n + 1} y^{n + 2}$$ which diverges for all $x,y\neq 0$. $\endgroup$ – Azlif Oct 31 '19 at 12:35

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.